Thrombocytopenia as a Side Effect of Heparin Therapy and COVID-19 Vaccination: A Review - S. S. Postnikov; N. V. Teplova; O. V. Gulbekova (Безопасность и риск фармакотерапии)
INTRODUCTION. Both low-molecular-weight and unfractionated heparins are frequently used to prevent and treat COVID-19-associated thrombosis, placing patients at an increased risk of developing heparin-induced thrombocytopenia (HIT) as an adverse reaction. Vaccination has played a key role in combating the COVID-19 pandemic, yet careful consideration is needed for potential adverse events following immunisation, in particular, for vaccine-induced immune thrombotic thrombocytopenia (VITT) associated with adenoviral vector vaccines.AIM. This study aimed to conduct a comparative analysis of HIT and VITT prevalence, pathogenetic mechanisms, clinical manifestation patterns, and treatment considerations in order to select the most effective therapeutic strategies for each condition and optimise them for clinical use.DISCUSSION. This comparative analysis covers full-text systematic reviews, meta-analyses, clinical trial reports, review articles, and case reports in Russian and English published from 1992 to March 2024 and retrieved from bibliographic databases, including PubMed.gov, Lens.org, and eLIBRARY.RU. According to the analysis, HIT incidence is higher in women who had previous cardiovascular or orthopaedic surgery, women on extracorporeal membrane oxygenation, and critically ill patients with COVID-19, whereas VITT is more common in women under 55 taking oral contraceptives and immunised with an adenoviral vector vaccine. The first signs of HIT usually show 5–10 days after heparin initiation, and the time of VITT onset varies from 4 days to 1 month. In contrast to HIT, VITT is characterised by atypical localisation of thrombosis. In HIT, platelet-activating anti-heparin/platelet factor 4 IgG antibodies bind to FcγRIIA receptors, which leads to platelet activation and aggregation. In VITT, the polyanion that triggers the immune system is either hexon protein or adenoviral vector DNA from neutrophil extracellular traps. Potential treatments for HIT include heparin discontinuation or switching from unfractionated heparins to low-molecular-weight heparins, fondaparinux sodium, or non-heparin anticoagulants (direct thrombin inhibitors and oral anticoagulants). Treatment options for VITT include non-heparin anticoagulants, fondaparinux sodium, and intravenous immunoglobulins. Switching to non-heparin anticoagulants in VITT is optional. Venous thrombosis is the main cause of death in both adverse reactions.CONCLUSIONS. Medical professionals should be alert to the potential development of VITT after vaccination with adenoviral COVID-19 vaccines and HIT during the use of heparins. Patients with suspected adverse reactions require prompt hospital admission, haematologist consultation, and laboratory and instrument testing.